Case Report: Sequential use of tezepelumab and mepolizumab for eosinophilic otitis media in EGPA: a steroid-sparing strategy - Matsuno, Osamu; Kawamoto, Masahiro; Wibowo, Tansri; Ishida, Yutaka; Ogata, Atsuhsi (Frontiers in Allergy, 2025)
Even in eosinophilic granulomatosis with polyangiitis (EGPA), not all manifestations of eosinophilic inflammation respond equally to anti–interleukin-5 (IL-5) therapy. We report a case of steroid-refractory eosinophilic otitis media (EOM) in a patient with EGPA, where systemic symptoms such as asthma and chronic rhinosinusitis initially responded to high-dose mepolizumab, but relapsed upon corticosteroid tapering. Introduction of tezepelumab led to marked improvement in EOM and upper and lower airway symptoms. To sustain remission, we employed a bi-monthly alternating regimen of tezepelumab and mepolizumab, achieving long-term control without dual biologic use or systemic corticosteroid escalation. This case highlights a personalized and steroid-sparing strategy for managing complex type 2 inflammation in EGPA.